Test Anxiety in Spanish Adolescents: Examining the Role of Emotional Attention, and Ruminative Self-focus and Regulation - Pena, Mario; Losada, Lidia (Frontiers in Psychology, 2017)
Emotional attention has been found as a key predictive dimension of stress. However, very few studies have investigated the relationship between emotional attention and test anxiety. The objective of the present study was to analyze the role of emotional attention, measured using the Trait Meta-Mood Scale (TMMS), on the level of test anxiety, and measured using the Test Anxiety Inventory (TAI). In addition, we examined the potential mediating role of Self-Rumination and Self-Reflection, as measured through the Rumination-Reflection Questionnaire (RRQ), on the relationship between emotional attention and test anxiety. The sample included 385 Spanish adolescents between 14 and 19 years of age. Mediation analysis results are consistent with a model in which Self-Rumination, but no self-Reflection, mediates the relationship between Emotional Attention and Test Anxiety. Finally, several potential implications of these findings to improve quality of life in adolescents are discussed.